Additive amelioration of ALS by co‐targeting independent pathogenic mechanisms. Issue 2 (11th January 2017) - Frakes, Ashley E.; Braun, Lyndsey; Ferraiuolo, Laura; Guttridge, Denis C.; Kaspar, Brian K.
Abstract: Objective: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease in which glia are central mediators of motor neuron (MN) death. Since multiple cell types are involved in disease pathogenesis, the objective of this study was to determine the benefit of co‐targeting independent pathogenic mechanisms in a familial ALS mouse model. Methods: Recently, our laboratory identified that ALS microglia induce MN death in an NF‐ κ B‐dependent mechanism. We also demonstrated that a single, post‐natal, intravenous injection of adeno‐associated viral vector serotype 9 encoding a shRNA against mutant SOD1 is able to traverse the blood–brain barrier of ALS mice and reduce SOD1‐expression in astrocytes and MNs. Reducing mutant SOD1 in MNs and astrocytes led to a robust increase in survival. To evaluate the benefit of co‐targeting multiple cell types in ALS, we combined microglial NF‐ κ B suppression with SOD1 reduction in astrocytes and MNs. Results: Targeting both astrocytes and microglia resulted in an additive increase in survival and motor function by delaying both onset and progression. Strikingly, targeting all three cell types (astrocytes, motor neurons [MNs], and microglia) resulted in an additive increase in lifespan and motor function, with maximum survival reaching 204 days, 67 days longer than the mean survival of untreated control animals. Interpretation: Our data suggest that a combinatorial approach co‐targeting different pathogenic mechanisms in independent cell types is a beneficial therapeutic strategy for ALS.